Experiences and perceptions of women involved in food garden projects in Khayelitsha - Ndlovu, Sibusiso (Department of Social Development, 2015)
The purpose of this study was to explore the experiences and perceptions of women involved in food garden projects. This was evaluated against the Community Driven Development approach which is a development initiative to empower community groups by giving them control over resources and decision making in their efforts to improve their living conditions. The context in which the seventeen women who participated in the study live is one of poverty. Many women in the study mentioned lack of employment as their motivation for joining food gardens, which they saw as a way of escaping poverty and providing food for their households. An exploratory and descriptive study was conducted to obtain information from the women involved in food gardens as it allowed the researcher to gain data in an open, flexible and inductive manner. This research design was appropriate for the study as research participants were best understood within their natural setting. Seventeen face-to-face, in-depth interviews were conducted. The participants’ ages ranged from twenty-eight to sixty years old. The majority of the women interviewed were in their fifties. A semi-structured interview schedule was used as a guideline and was however, not followed rigidly. Data was collected through an audio recorder and consent forms were signed by the participants. Transcription was done using Tesch’s (1990) method of analysis. The findings indicated that food gardens provide an opportunity to the women to take action to sustain their livelihoods, providing a form of self employment, food and a means to generate some income. The food gardens also created social networks for these women which resulted in them being included in the community’s activities as they had developed networks which acted as sources of support. However, the women repeatedly iterated that lack of funds and inconsistent support from role players such as government and other agencies hindered the success of their activities. Their main comments on recommendations for assistance and support were directed to the government and other organisations working with people in the grassroots level. Support for these local initiatives may contribute to their success.